P1712INFLUENCE OF DONOR AGE ON KIDNEY GRAFT SURVIVAL. (6th June 2020) - Grande Cabrerizo, Carmen; Calvillo, Jorge; Pérez valdivia, Miguel Ángel; Suñer Poblet, Marta; Suarez Benjumea, Alejandro; Gasco Martos, Blanca
Abstract: Background and Aims: Kidney transplantation is the treatment of choice in patients with end stage kidney disease (ESKD). In recent years, donation activity and kidney transplant in Spain has suffered a significant increase, accompanied by a change in the profile of donors to cope with the waiting list. It has been produced a decrease in mortality due to traffic accidents, the main source of donation, in contrast, strokes are currently the main source. The donor is of older age and with greater morbidity, especially cardiovascular, which makes doubts about its functionality and Whether this is an adequate strategy to expand the donor pool. The objective To analyze if the survival of the graft is worse in donors of very advanced age with respect to other groups of expanded criteria deceased donors. Method: A retrospective analysis was carried out with data from SICATA regarding kidney transplant from a deceased donor with age ≥55 years made between 1/1/06 -12/31/15 at the Virgen del Rocío University Hospital. The graft failure was defined as return to dialysis. 495 cases were obtained, which were divided by the age of the donor in three groups: between 55-65 (N = 310), between 66 -75 (N = 154) and> 75 (N = 31). These groups were compared in terms of graft survival (censored for death) using analysis of survival Kaplan-Meier log-rank. We also performed a multivariate analysis of risk-adjusted graft survival using the Cox proportional hazard technique with the relevant predictive factors and the age of the donor, as a categorical and continuous variable. Analysis with SPSS 24.0. Results: The table shows the comparisons between the different population groups and in the Figure is shown the survival functions for each one. Taking into account those results, it cannot be concluded that the age of the donor in these different age groups has significant influence on graft survival with the data we handle. The multivariate analysis concluded that, for this population group and the data handled, the variables that influence the failure of the graft are: the height of the donor, the sex of the recipient and the time in renal replacement therapy. In no case does the age of the donor influence the survival of the graft. Conclusion: Kidney transplant improves survival and quality of life in comparison with dialysis long term. Our data did not show significant differences between the different groups of age, which indicates that the use of kidney grafts from elderly donors is acceptable and can greatly expand the donor group. The decision to use or not a kidney elderly donor should be based on the individual characteristics of the donor, as well as in other factors related to the standard clinical criteria for kidney transplant.